Intercomparison of flatness measurements of an optical flat at apertures of up to 150 mm in diameter. (20th January 2017) - Quabis, S; Schulz, M; Ehret, G; Asar, M; Balling, P; Křen, P; Bergmans, R H; Küng, A; Lassila, A; Putland, D; Williams, D; Pirée, H; et al.
Abstract: Recently, a scientific comparison of flatness measuring instruments at European National Metrology Institutes (NMIs) was performed in the framework of EURAMET. The specimen was a well-polished optical surface with a maximum measurement aperture of 150 mm in diameter. Here, we present an evaluation concept, which allows the determination of a mean flatness map taking into account different lateral resolutions of the instruments and different orientations of the specimen during measurement. We found that all measurements are in agreement with the mean flatness map within the uncertainty intervals stated by the participants. The aim of this scientific comparison is to specify an appropriate operation and evaluation procedure for future comparisons.